Polio vaccination and marginal effects among children aged 12–23 months in Lesotho using 2024 LDHS data: A multilevel analysis approach - Kassahun Animut Metkie; Yordanos Sisay Asgedom; Seblewongel Gebretsadik Sertsewold; Mesfin Abebe; Amanuel Yosef Gebrekidan; Tsion Mulat Tebeje (PLoS ONE, 2025)
Background Infectious diseases that have affected countless newborns, children, and adults can be avoided with polio vaccination. The WHO and Lesotho’s health strategy placed a strong emphasis on vaccination as a means of preventing and controlling infectious diseases. The current study’s goal was to indicate marginal effects and identify the determinants of polio vaccination status in children between the ages of 12 and 23 months. Methods The polio vaccination status in Lesotho was evaluated using LDHS data collected from 490 children aged 12–23 months. The prevalence of polio vaccination was presented through frequencies and percentages. The heterogeneity in child polio vaccination status across clusters was determined using the ICC value and the chi-square test. The data was analyzed using a multilevel ordinal model, and model selection was based on IC values. Results The descriptive findings of the study revealed that approximately 29.6% of children were not fully vaccinated against polio. The use of multilevel analysis was deemed appropriate based on a significant chi-square result (p-value = 0.033). Clusters accounted for approximately 15.9% (ICC = 15.88) of the overall variation in polio vaccination status among children. The final adjusted random intercept PO model indicated a significant relationship (p-value < 0.05) between children’s polio vaccination status and factors such as district type, health facility visits in the past 12 months, number of ANC visits, place of delivery, and family size. The marginal effects of these key variables were also significant for each category of polio vaccination status. Conclusions In Lesotho and around the world, polio vaccination is a crucial health measure to enhance children’s development. Approximately 29.6% of the children in the study were not fully vaccinated. These rates differed by district and the number of ANC visits the moms had. Treatments and safeguards for children’s health should be more focused on enhancing medical facilities and services and encouraging ANC visits to receive care.